Predicting wasteful spending in tree planting programs in Indian Himalaya. (June 2022) - Rana, Pushpendra; Fleischman, Forrest; Ramprasad, Vijay; Lee, Kangjae
Highlights: There is a substantial risk of failure from natural climate solutions. Tree planting programs target areas with high tree cover or high probability of tree cover loss. Ineffectivenatural climate solutions fail to sequester additional carbon. Government-run target-based tree planting programs have led to substantial waste of resources. Abstract: Tree planting is widely promoted as a cost-effective natural climate solution, yet there are few evaluations of the implementation of tree planting. Our analysis of a unique dataset on tree planting in the Indian Himalayan state of Himachal Pradesh shows that over half of the state's budget for tree planting is wasted on plantations that are unlikely to survive and/or are poorly designed to achieve the state's goal of increasing forest cover. Himachal Pradesh (and India more generally) has been identified as a high potential area for natural climate solutions due to high government capacity, adequate funding, and government agencies with extensive planting experience. We combine data on the location and financial outlay for plantations, which allow us to analyze the relationship between plantations and social and biophysical conditions, with a machine learning model, trained on past land cover change, which predicts the likelihood of future tree cover loss in plantation areas. Our finding that even in this high potential area tree planting programs involve considerable wasted expenditure on ineffective plantations raises questions about optimistic assessments of the potential for tree planting to serve as a cost-effective natural climate solution. We suggest deemphasizing the target-based approaches that dominate present policy-making and high-profile scientific publications, which we argue are the cause of wasted expenditures in Himachal Pradesh. Instead policy-makers and scientists interested in natural climate solutions should focus on developing solutions that respond to local biophysical, social, and economic realities, and are implemented through transparent procedures that increase accountability to and reinforce the rights of forest dependent people.